Entre rencontres et rendez-vous : stratégies marocaines de sexualité hors mariage - Matthew Carey (L’Année du Maghreb)
Whatever the social background, premarital sexuality in Morocco poses a number of particularly sensitive problems, both practical and moral. However these problems are shaped differently and affect social actors in different ways depending on whether they live in big cities, in the plains just outside urban areas or in the remote desert and mountain areas. Our article addresses these dilemmas and resulting differences, based on an analysis that allows for variations between the plains and mountains on the one hand, and encounters and rendezvous on the other hand. We found that in remote areas, the social environment and behaviors allow, sometimes encourage, intersexual encounters, but strongly oppose the possibility of romantic dates, while in the plains circumstances leave room for organizing rendezvous, but make it difficult for encounters to happen. Our article also explores the impact of new technologies on these interactions, the role of mobility and wish for anonymity.